An Islamic interpretation of tragic hero in Shakespearean tragedies - Abdul Manaf, Nor Faridah (IIUM Research Centre, 2004)
The Islamic concept of 'tragic hero' is studied in comparison to concepts already accepted in the West, bringing in arguments from the Judaeo-Christian-Islamic traditions.In this study, the concept of 'tragic hero' is revisited according to an Islamic framework and a reading of the three states of selves (or nafs) first mentioned in the Quran.